Pemberdayaan Masyarakat Dalam Meningkatkan Pengetahuan Ibu Tentang Pemberian Imunisasi Pada Bayi Usia 0-12 Bulan di Kelurahan Mangga Kecamatan Medan Tuntungan - Emelia Apriani Tampubolon; Rizky Andriani Bakara (Indonesian Journal Publisher, 2021)
Immunization is the provision of immunity against a disease and will only provide immunity or resistance to that disease, so if you need to avoid various diseases, other immunizations are needed. Immunization is very effective in preventing infectious diseases, through immunization our bodies will not be susceptible to infectious diseases (Faisal, 2021). There are two types of immunization, namely active immunization and passive immunization. National immunization programs include BCG, Hepatitis B, DTP, Polio, Hib and measles.The subjects in the service activities are mothers who have babies aged 0-12 months in Mangga Village, Ladang Bambu District, as many as 12 people. In the initial stage, an approach was made to the residents to deliver counseling material using the lecture method, immunization implementation assisted by the village midwife and followed by a question and answer session. Community service activities with the title